A narrative meta‐review of a series of systematic and meta‐analytic reviews on the intervention outcome for children with developmental co‐ordination disorder. (30th December 2016) - Miyahara, M.; Lagisz, M.; Nakagawa, S.; Henderson, S. E.
Summary: Background: Systematic reviews and meta‐analyses are considered to be the 'gold standards' for synthesizing research evidence in particular areas of enquiry. However, such reviews are only useful if they themselves are conducted to a sufficiently high standard. The aim of this study was to conduct a narrative meta‐review of existing analyses of the effectiveness of interventions designed for children with developmental co‐ordination disorder (DCD). Methods: A narrative meta‐review of systematic and meta‐analytic reviews aimed at evaluating the effectiveness of intervention for children with DCD was conducted on studies published between 1950 and 2014. We identified suitable reviews, using a modification of the Population, Intervention, Comparison, Outcome (PICO) system and evaluated their methodological quality using the Assessment of Multiple Systematic Reviews (AMSTAR). In addition, the consistency of the quality of evidence and classification of intervention approaches was assessed independently by two assessors. Results: The literature search yielded a total of four appropriate reviews published in the selected time span. The Assessment of Multiple Systematic Reviews percentage quality scores assigned to each review ranged from 0% (low quality) to 55% (medium quality). Evaluation of the quality of evidence and classification of intervention approaches yielded a discrepancy rate of 25%. All reviews concluded that some kind of intervention was better than none at all. Conclusions: Although the quality of the reviews progressively improved over the years, the shortcomings identified need to be addressed before concrete evidence regarding the best approach to intervention for children with DCD can be specified.